Ectomycorrhizal Networks in the Anthropocene: From Natural Ecosystems to Urban Planning - Authier, Louise; Violle, Cyrille; Richard, Franck (Frontiers in Plant Science, 2022)
Trees acquire hydric and mineral soil resources through root mutualistic associations. In most boreal, temperate and Mediterranean forests, these functions are realized by a chimeric structure called ectomycorrhizae. Ectomycorrhizal (ECM) fungi are highly diversified and widely vary in their specificity toward plant hosts. Reciprocally, association patterns of ECM plants range from highly specialists to generalists. As a consequence, ECM symbiosis shapes interaction networks which mediate plant-plant nutrient fluxes among interconnected individuals, and drive plant community dynamics. Our knowledge of ECM networks essentially relies on a corpus acquired in temperate ecosystems, whereas the belowground facets of both anthropogenic ECM forests worldwide and inter-tropical ecoregion remain poorly investigated. Here we successively 1) review the current knowledge of ECM networks, 2) examine the content of early literature produced in ECM agroforests, 3) analyze the recent progress that has been made in understanding the place of ECM networks in urban soils and 4) provide directions for future research. From the examined corpus of knowledge, we gather three main conclusions. First, the emergence of metabarcoding tools has propelled a resurgence of interest in applying network theory to ECM symbiosis. These methods revealed an unexpected porosity between mutualists guilds of plants. Thus, vesicular mycorrhizal (VA) herbaceous plants embed ECM mycelia through root endophytic interactions. This affinity of ECM fungi to bind VA and ECM plants questions on the nature of the associated functions. Second, despite the central place of ECM trees in both managed and cultivated forests, few attentions have been paid to provide a systemic view of these man-made landscapes. Third, we report the current lag to apply ECM network theory to urban soils, while management initiatives flourished in order to interconnect motile organisms through ecological corridors. We identify the reasons underlying the highly challenging nature of interconnecting fixed organisms in urban greenspaces. In particular, we report 1) the pauperized nature of resident ECM inoculum and 2) a spatial conflict between belowground human pipelines and ECM networks. We finally identify the main directions of future research to make the needed anastomosis between the current picture of plant functioning and the understanding of belowground ECM networks.